Service model based on lean tools to improve order fulfillment rate in a SMEs in the commercial sector (LACCEI, 2024)
The commercial sector has maintained a uniform growth during the last years. However, there are problems within logistics that harm customer satisfaction, companies aim to deliver orders on time and avoid large losses. That said, in the present research, the problem that generates the greatest economic loss for the company is the high percentage of unfulfilled orders. Therefore, it is proposed the implementation of a model based on the Lean methodology, through the application of 5S, ABC and Kanban with the objective of reducing the non-fulfillment of orders. The research focuses on a warehouse where the root causes of the problem are identified and quantified, to later attack them through Lean tools. Finally, the proposed model achieves a reduction of 38.8%, 12.32% and 47.23% in picking times, system registration and total simulation time, respectively, and thus improves customer delivery compliance to reach the 5% objective.